2013
DOI: 10.1155/2013/925062
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Serum Level of s-Met (Soluble Hepatic Growth Factor Receptor) and Preeclampsia in the First and Second Trimesters of Pregnancy

Abstract: Introduction. Preeclampsia (PE) is an important cause of mortality and morbidity for mothers, fetuses, and the newborns. Placenta plays a pivotal role in pathogenesis of PE. Hepatic growth factor (HGF) is a cytokine expressed by the mesenchymal stalk of placental villi during pregnancy and assumes a paracrine role in trophoblasts which express its receptor (c-MET). In the present study, we investigate the diagnostic value of s-Met (the soluble form of the receptor) in the first and second trimesters of pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…We analyzed the concentration of plasma sMet and found that plasma sMet peaked at E10.5 in most of the CD1 pregnant mice. Consistently, plasma sMet levels also peak during mid-term pregnancy in normal pregnant women [20,21]. To some extent, our data suggest that HGF/c-Met signaling regulates placental cell functions in humans and mice in a similar manner and that CD1 pregnant mice could be a suitable animal model to study the function of HGF/c-Met signaling (Table 1).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We analyzed the concentration of plasma sMet and found that plasma sMet peaked at E10.5 in most of the CD1 pregnant mice. Consistently, plasma sMet levels also peak during mid-term pregnancy in normal pregnant women [20,21]. To some extent, our data suggest that HGF/c-Met signaling regulates placental cell functions in humans and mice in a similar manner and that CD1 pregnant mice could be a suitable animal model to study the function of HGF/c-Met signaling (Table 1).…”
Section: Discussionsupporting
confidence: 76%
“…The concentration of plasma sMet peaked at E10.5 in the majority of CD1 mice sMet is the soluble form of c-Met, formed after metalloprotease hydrolysis, and it hinders HGF binding to c-Met to a certain extent [7]. Plasma sMet levels peak during the second trimester (21-26 weeks) in humans [20,21], but the dynamic change of plasma sMet in pregnant mice is unclear. ELISA was performed to analyze the dynamic changes in plasma sMet levels at different time points throughout pregnancy in CD1 mice.…”
Section: The Localization Of Hgf and C-met During The Development Of Mid-placenta In Cd1 Micementioning
confidence: 99%
“…85 These findings are consistent with the reports of reduced HGF production by the PE placentas 87 and reduced soluble Met (s-Met) in the blood of PE mothers. 88…”
Section: Migration Stimulation By Chemokines and Hgfmentioning
confidence: 99%
“…The expansion of new lymphatic vessels from pre-existing ones, called lymphangiogenesis, is controlled mainly by growth factors, i.e., VEGFs such as VEGF-C and its ligand VEGFR-3, VEGF-D [53,54,55], and other factors, i.e., hypoxia-inducible factor 1-α (HIF-1α), the Tie/angiopoietin system, neuropilin-2, and integrin-α 9 [56,57,58,59,60,61]. However, until recently, there was a paucity of data on the lymphatic profile during pregnancy and in PE [62,63,64].…”
Section: Lymphangiogenesismentioning
confidence: 99%
“…The aforementioned groups instead observed a stromal network immunostained with podoplanin. Lymphangiogenesis was observed at the decidua [68,69,70,71,72] and the uterine wall [64,73].…”
Section: Lymphangiogenesismentioning
confidence: 99%